Characteristics of SARS-CoV-2 positive cases beyond health-care professionals or social and health-care facilities - Giovanna Deiana; Antonio Azara; Marco Dettori; Fiorenzo Delogu; Gavino Vargiu; Isabella Gessa; Antonella Arghittu; Marcello Tidore; Giorgio Steri; Paolo Castiglia (BMC, 2021)
Abstract Background During the outbreak of SARS-CoV-2 in Italy, infection among health-care professionals and in the context of welfare and health-care facilities was a significant concern. It is known that the elderly or those with concomitant pathologies are at greater risk of a serious evolution of the disease if affected by COVID-19 and that health workers are a category with greater exposure to SARS-CoV-2 infection. Until now, there has been little information on the epidemiological features and transmission dynamics of the COVID-19 outbreak which did not involve health-care professionals or social and health-care facilities. For this reason, this paper aims to describe the epidemiological characteristics of SARS-CoV-2 infection in the general population outside these semi-closed communities. Methods The study was designed by analyzing the data of the 1371 SARS-CoV-2 positive subjects observed in Sardinia up to 9 July, 2020 and whose data were available in the public health department. Statistical analysis and graphic representation were performed using STATA and Adobe Illustrator, respectively. Results Of the positive cases analyzed, 323 (23.5%) are health-care workers and 563 (41.1%) reside in social or health-care facilities. The number of positive cases among the general population (subjects who do not belong to these semi-closed communities), is 399 (29.1%), 208 females and 191 males. The estimated Case Fatality Rate stands at 5.0%, which is almost half the rate reported for all the SARS-CoV-2 positive cases (9.8%). The geographical distribution of positive cases differs considerably from the distribution of the totality of cases in Sardinia. Conclusions This review provides an insight into the COVID-19 situation in the general community, ie not involving health-care professionals or social and health-care facilities. Understanding the evolving epidemiology and transmission dynamics of the outbreak outside of these semi-closed communities would provide appropriate information to guide intervention policy. The COVID-19 pandemic has exacerbated the vulnerability of our health-care system. Severe disruptions in care, medicine shortages and unequal access to health-care are but a few examples of the challenges faced by people living in Italy and Europe, highlighting the importance of evidence-based approaches in supporting the development of prevention and response strategies for future pandemics.